Data Policy Finder: an easily integratable tool connecting data librarians with researchers to navigate publication requirements. - Dellureficio, Anthony J.; Willoughby, Eric; Gibson, Donna S. (Journal of the Medical Library Association, 2024)
The Data Policy Finder is a searchable database containing librarian-curated information, links, direct quotes from relevant policy sections, and notes to help the researcher search, verify, and plan for their publication data requirements. The Memorial Sloan Kettering Cancer Center Library launched this new resource to help researchers navigate the evergrowing, and widely varying body of publisher policies regarding data, code, and other supplemental materials. The project team designed this resource to encourage growth and collaboration with other librarians and information professionals facing similar challenges supporting their research communities. This resource creates another access point for researchers to connect with data management services and, as an open-source tool, it can be integrated into the workflows and support services of other libraries.